2020
DOI: 10.3390/su12229401
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Local Green Space and Human Mobility Patterns during COVID-19 for Maryland and California, USA

Abstract: Human mobility is a significant factor for disease transmission. Little is known about how the environment influences mobility during a pandemic. The aim of this study was to investigate an effect of green space on mobility reductions during the early stage of the COVID-19 pandemic in Maryland and California, USA. For 230 minor civil divisions (MCD) in Maryland and 341 census county divisions (CCD) in California, we obtained mobility data from Facebook Data for Good aggregating information of people using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 40 publications
4
35
0
1
Order By: Relevance
“…Recent studies have demonstrated that patterns of visiting natural spaces such as urban parks and woodlands have changed as a result of COVID-19 [ 2 , 14 ]. Other studies have called for keeping parks and green spaces accessible during the COVID-19 pandemic due to their health benefits [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that patterns of visiting natural spaces such as urban parks and woodlands have changed as a result of COVID-19 [ 2 , 14 ]. Other studies have called for keeping parks and green spaces accessible during the COVID-19 pandemic due to their health benefits [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study indicated that in the US, while mobility generally decreased during the pandemic compared to earlier (e.g., 13% lower for retail and recreation), mobility to parks increased 54% [ 30 ]. A recent US study suggested that daily human mobility during the early phase of the COVID-19 outbreak (March–April 2020) decreased less in communities with a higher amount of vegetation after stay-at-home orders indicating the potential impact of and disparities in greenspace access during a pandemic [ 31 ]. To date, almost no research has studied the intersection of these complex systems to understand how the pandemic affected the use of greenspace and the associated psychosocial effects.…”
Section: Introductionmentioning
confidence: 99%
“…There was linear confinement at first, with the population avoiding all sorts of places and staying at home. After that period, when the virus was unknown, it was understood that parks and green areas were lowrisk areas and provide physical and mental well-being during the lockdown [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%